2003
DOI: 10.1007/s00775-002-0402-y
|View full text |Cite
|
Sign up to set email alerts
|

Ligand effects on the binding of cis- and trans-[PtCl2Am1Am2] to proteins

Abstract: As part of a systematic study of the basic principles that govern the formation and reactivity of Pt-protein adducts, we report the effect of substituting the amine ligand of cis- and trans-[PtCl(2)(NH(3))(2)] complexes with bulkier planar aromatic or nonplanar cyclic amine ligands on the binding properties of the complexes to ubiquitin and to horse heart myoglobin. The ligand replacement had a different effect on the cis or trans isomers investigated. In the cis-Pt complexes, replacing one or both amine ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
3
41
0
Order By: Relevance
“…PI is a DNA intercalator that passes through the cell membrane and goes to the nucleus when the cell membrane integrity has been lost. So, in a typical annexin V-PI scattergram the annexinV À /PI À cell population (left bottom quadrant) contains alive cells, the annexinV + /PI À cell population (right bottom quadrant) contains cells experiencing early PCD, the annexinV + /PI + cell population (right upper quadrant) contains cells undergoing late PCD, and finally, the annexinV À /PI + cell population (left upper quadrant) contains necrotic cells [19]. Fig.…”
Section: Programmed Cell Death (Pcd) Induction In L Infantum Promastmentioning
confidence: 97%
See 1 more Smart Citation
“…PI is a DNA intercalator that passes through the cell membrane and goes to the nucleus when the cell membrane integrity has been lost. So, in a typical annexin V-PI scattergram the annexinV À /PI À cell population (left bottom quadrant) contains alive cells, the annexinV + /PI À cell population (right bottom quadrant) contains cells experiencing early PCD, the annexinV + /PI + cell population (right upper quadrant) contains cells undergoing late PCD, and finally, the annexinV À /PI + cell population (left upper quadrant) contains necrotic cells [19]. Fig.…”
Section: Programmed Cell Death (Pcd) Induction In L Infantum Promastmentioning
confidence: 97%
“…1. The synthetic methods leading to the synthesis of compounds 1-4 are based on the trans effect of Pt(II) complexes so that the trans geometry of the synthesized compounds is guaranteed [19]. These compounds exhibit a good water solubility having a limit of solubility of 1 mg/mL.…”
Section: Synthesis Of Compounds 1-3mentioning
confidence: 99%
“…In a more recent study we reported that for trans compounds such as trans-[PtCl 2 (NH 3 )(Am)], where Am = 4-picoline and piperidine, substitution of one small ammine ligand of transplatin with either bulky planar aromatic or with non-planar heterocyclic amines does not decrease the binding rate of the divalent Pt complex to the protein [19]. The 1:1 platination reactions of ubiquitin with 1-2 mM of platinum complexes I-III, at 37°C, were monitored by ESIMS.…”
Section: Reactions With Ubiquitinmentioning
confidence: 99%
“…A recent review summarizes the progress made in the applications of modern analytical methodologies for antitumor metallodrug-protein studies [20]. ESI-MS was recently shown as an extremely useful tool for studying the cisplatin-protein interactions [19,[21][22][23][24][25]. Also, HPLC [19,24,[26][27][28] and a complementary high-resolution technique with an orthogonal separation mechanism, CE [29][30][31], are growing in importance for characterizing the protein binding for different metal complexes.…”
Section: Introductionmentioning
confidence: 99%